Characterization and surface-enhanced Raman spectral probing of silver hydrosols prepared by two-wavelength laser ablation and fragmentation - Smejkal, Petr; Sisková, Karolína; Vlcková, Blanka; Pfleger, Jirí; Sloufová, Ivana; Slouf, Miroslav; Mojzes, Peter (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2003)
A four step Ag foil laser ablation-Ag nanoparticle fragmentation procedure in ultrapure water was carried out both under argon and in air. Pulses of a high power Nd/YAG laser were used for laser ablation (1064 nm) and for the three step Ag hydrosol treatment in the absence of Ag foil in the sequence 1064-532-1064 nm. Transmission electron microscopy (TEM) and surface plasmon (SP) extinction spectra provide evidence of Ag nanoparticle fragmentation in the second and third step of the procedure carried out under argon. While polydispersity of Ag hydrosol increases in the second step, both the polydispersity and the mean size of the nanoparticles are reduced in the third step. Qualitative and quantitative surface-enhanced Raman scattering (SERS)/surface-enhanced resonance Raman scattering (SERRS) spectral probing of systems with Ag hydrosols and the selected adsorbates at 514.5 nm excitation shows that Ag hydrosols obtained in the second step of the preparation procedure carried out in air are the most suitable substrates for SERS/SERRS experiments performed at this excitation wavelength.
Keywords: Spectrum Analysis, Raman; Silver Compounds; sloučeniny stříbra; Ramanova spektroskopie